Analisis pengaruh persepsi kemudahan, keamanan, dan kualitas pelayanan penggunaan QRIS terhadap inklusi keuangan generasi z di coffee shop Bandar Lampung dalam perspektif ekonomi Islam - Alvira, Riza; Iqbal, Muhammad; Dedi Satriawan (AL-Muqayyad, 2025)
Generation Z, born between 1997 and 2012, is recognized as a tech-savvy cohort that prefers digital payment methods over cash. This study aims to analyze the influence of perceived ease of use, perceived security, and service quality on the financial inclusion of Generation Z using QRIS (Quick Response Code Indonesian Standard) as a digital payment method. A quantitative research approach was employed, with data collected through Google Forms questionnaires distributed to Generation Z individuals visiting coffee shops in Bandar Lampung. The sampling technique followed Lemeshow’s method, with 100 respondents, and variables were measured using a Likert scale. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results indicate that perceived ease of use and perceived security of QRIS significantly influence Generation Z’s financial inclusion. However, coffee shop service quality does not have a significant effect. These findings provide practical implications for strategies to enhance QRIS adoption in supporting financial inclusion while offering insights from an Islamic economics perspective in the context of digital payments